Manières de penser dans l'antiquité mediterranéenne et orientale : mélanges offerts à Francis Schmidt par ses élèves, ses collègues et ses amis - Batsch, Christophe.; Schmidt, Francis.; Vârtejanu-Joubert, Madalina. (Supplements to the Journal for the Study of Judaism, 2009)
Francis Schmidt's works in various fields of religious studies (mainly ancient Judaism), can be characterized by three words: historiography, anthropological history, and comparatism. In that respect he placed himself in the continuation of previous French scholars, such as Maurice Halbwachs or Pierre Vidal-Naquet. Francis Schmidt also played an essential role in transmitting to a new generation of scholars the complex issues and debates concerning the Dead Sea scrolls and Qumranic research. The papers offered in this volume share all the same interest in ancient religions and the methodological devices previously mentioned. They offer a rare example of a large comparatism between Assyrian, Greek, Roman, Jewish, and Christian approaches of some essential social or intellectual issues, by some of the most competent specialists in each field.